Status of Farming and Marketing of Live Pangas (Pangasius hypophthalmus) from Trishal Upazila to Different Areas of Bangladesh - Hossain, MI; Shikha, FH; Ahmmed, F (Journal of Environmental Science and Natural Resources, 2021)
The research was conducted to collect information on the status of farming and marketing of live pangas (Pangasius hypophthalmus) from Trishal region to different areas of Bangladesh by interviewing stakeholder and secondary sources. The survey was carried out for seven months from May to November, 2016. Pangas farmers, arotdar, commission agents, wholesaler and retailers were interviewed in accordance with participatory rural methods. The results showed that the best harvesting season were found to be June to July and November to January. It was also found that 90% farmers harvested their fish completely and only 10% of farmers harvested partially. The price of pangas depends on market structure, quality, size, distance, weight, seasonal variation and regional perception. The prices of pangas were found to be highest of 130tk/kg and the lowest of 85tk/kg but sometimes 60 to 70tk/kg when the fish are dead (on the way to destined area) in different districts. On the other hand significant quantity loss was observed in fish 8%, 10%, 15%, 18%, and 19% after reaching to Savar, Manikgonj, Maowa, Sylhet, and Barisal from Trishal. Therefore, it was strongly recommended that proper handling of live fish must be ensured during transportation to attain quality pangas at consumer level. Environ. Sci. & Natural Resources, 12(1&2): 73-82, 2019